Electrochemical Characterization of Laboratory Fabricated Bromide Ion Selective Electrode - Nyachhyon, Armila Rajbhandari; Manandhar, Krishna; Pradhananga, Raja Ram (Journal of Institute of Science and Technology, 2016)
Bromide ion selective electrode (Br-ISE) have been successfully fabricated in the laboratory. The polycrystalline Ag2S-AgBr membrane material of Br-ISE was prepared by co-precipitation of silver sulphide and silver bromide from aqueous solution and was characterized by X-ray diffractometry (XRD). XRD results showed that material is in mixed phase state having Ag3SBr, Ag2S and AgBr. Scanning electron microscopy (SEM) has been used to study the texture of the surface. The potentiometric response has been investigated by 2 electrode system whereas 3 electrode systems have been used for electrochemical impedance spectroscopy (EIS). The electrode was found to behave well up to the bromide concentration of 1x10-5M with a Nernstian slope of 58 mV per decade change in bromide ion concentration. The selectivity coefficient of electrode containing bromide ion in the presence of I- and Cl- ions was found to be 3.98 and 8x10-2, respectively indicating that I- and Cl- ions interfere in the response of bromide electrode to bromide ion. The EIS studies shows that the charge transfer process is the key mechanism that is going on at the electrode/ electrolyte interface and electrode/ back contact interface. Journal of Institute of Science and Technology Vol. 21, No. 1, 2016, page: 76-81